Emily Taylor, dean of women: inter-generational activism and the women's movement at the University of Kansas - Sartorius, Kelly C. (Kansas State University, 2011)
Historians have often linked the route of the second wave of the women's movement on college campuses with the development of women's liberation as young women involved in the New Left came to feminist consciousness working in civil rights and anti-Vietnam protests. This dissertation considers a “longer, quieter” route to feminist consciousness on a college campus by considering the role of a dean of women, Dr. Emily Taylor, at the University of Kansas between 1956 and 1974. Through her office that centered on women’s affairs, Taylor used the student personnel and counseling profession to instigate the dissolution of parietals at KU, a project that has long been associated with New Left student protests. A liberal feminist committed to incremental change to benefit women’s equal status in society, Taylor structured her office to foster feminist consciousness in undergraduate students, and provided staff support to New Left and radical women’s groups as they emerged on the KU campus. As a result, the inter-generational exchange that occurred within the KU dean of women’s office illustrates one example of how liberal and radical feminists interacted to foster social change within an institution of higher learning. The projects undertaken within her office illustrate that these seemingly separate groups of women overlapped, collaborated, and sometimes clashed as they worked toward achieving feminist goals. Her career at KU also shows that the metaphor of a first and second wave of the women’s movement may not be an accurate picture of the growth of feminism on co-educational campuses. Little scholarly work exists on the role of deans of women in higher education, or regarding women college students in the years immediately following World War II. This dissertation adds to the literature in both areas, showing that in the case of KU the administration was not a monolithic obstacle to student protest, the New Left, civil rights, and feminism. Instead, Taylor as dean of women pushed initiatives that bore on all of these areas. While Taylor is one example, her career illustrates patterns in deans of women’s activities that deserve further study and consideration.
Keywords: Women's studies; Education history; Higher education; History of American feminism; Student protest; American History (0337); History of Education (0520); Women's Studies (0453)